2020
DOI: 10.1186/s13690-020-00452-9
|View full text |Cite
|
Sign up to set email alerts
|

Women’s knowledge, attitude, and practice of breast self- examination in sub-Saharan Africa: a scoping review

Abstract: Background Breast cancer (BC) is a non-communicable disease with increased morbidity and mortality. Early detection of BC contributes to prompt linkage to care and reduction of complications associated with BC. Breast self-examination (BSE) is useful for detecting breast abnormalities particularly in settings with poor access to healthcare for clinical breast examination and mammography. Therefore, we mapped evidence on women’s knowledge, attitude, and practice of BSE in sub-Sahara Africa (SSA). Methods We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 55 publications
2
18
0
1
Order By: Relevance
“…A recent scoping review on BSE among women in SSA demonstrates limited published research and revealed varied level of knowledge ranging from 8.7% [ 5 ] to 98.9% [ 7 ] and practice ranging from 11.7% to 78%. It further suggests that BSE practice remains a challenge in SSA [ 8 ]. In Ethiopia, studies regarding BSE largely focused on health care workers and health science students and were conducted in large cities of the country mainly at referral hospitals [ 9 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent scoping review on BSE among women in SSA demonstrates limited published research and revealed varied level of knowledge ranging from 8.7% [ 5 ] to 98.9% [ 7 ] and practice ranging from 11.7% to 78%. It further suggests that BSE practice remains a challenge in SSA [ 8 ]. In Ethiopia, studies regarding BSE largely focused on health care workers and health science students and were conducted in large cities of the country mainly at referral hospitals [ 9 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…10 BSE has many benefits: easy to learn, cost-effective to the patient, high patient acceptability, and noninvasive procedure. [14][15][16][17] Other advantages are that it is a reasonably reliable procedure for early detection of breast cancer, it helps women to be familiar with their breasts and increases awareness of breast cancer and other breast cancer screening modalities such as CBE and mammography. [14][15][16][17] BSE also has some shortcomings like: it requires a lot of patient motivation for regular practice, can only detect palpable breast lesions, it increases benign breast biopsy rate, and there is difficulty in measuring adherence and competence.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Other advantages are that it is a reasonably reliable procedure for early detection of breast cancer, it helps women to be familiar with their breasts and increases awareness of breast cancer and other breast cancer screening modalities such as CBE and mammography. [14][15][16][17] BSE also has some shortcomings like: it requires a lot of patient motivation for regular practice, can only detect palpable breast lesions, it increases benign breast biopsy rate, and there is difficulty in measuring adherence and competence. 7 In low and medium-income countries, BSE is still very relevant as a means of cancer detection because up to 90% of the breast cancers in these regions are still self-detected.…”
Section: Introductionmentioning
confidence: 99%
“…A recent very comprehensive systematic review Udoh et al, [24] of most BSE researches done in the SSA concluded among others that there is "limited literature on women's attitudes towards BSE" (p.6). Thus, even among the extant predorminantly female literature, there is paucity in the Attitude domain of the whole BSE research area as a lot of the research effort into BSE in Sub-Saharan Africa (SSA) have focused on the knowledge and practice areas at the expense of attitude.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, even among the extant predorminantly female literature, there is paucity in the Attitude domain of the whole BSE research area as a lot of the research effort into BSE in Sub-Saharan Africa (SSA) have focused on the knowledge and practice areas at the expense of attitude. They recommended identification of, and evidentbased solutions to BSE contextual challenges when they wrote "…this study recommends further studies on knowledge, practice, and attitude of BSE, to identify contextual challenges and provide evidence-based solutions to improve women's knowledge, practice, and attitude of BSE in SSA…" [24] (p.1).…”
Section: Introductionmentioning
confidence: 99%